Interval Colourings of Some Regular Graphs - Kamalian, Rafayel R.; Petrosyan, Petros A . (Mathematical Problems of Computer Science, 2021)
A lower bound is obtained for the greatest possible number of colors in an interval colourings of some regular graphs.